On Several Important Issues on Legal Personality (Law and world, 2015)
This article aims at identifying problematic issues, which the current legislation of Georgia is silent about. These are the issues that are actively discussed throughout the world and today it represents the subject of modern legal-bioethical studies. The goal of this paper is to exactly identify each of these issues so that to continue further research on the problematic issues raised in the article, and to ﬁnd the ways of resolving them from the legal standpoint, which will be reﬂected in the eﬀective legislation, and break the silence in the legislation and address intentional or unintentional ignorance regarding the signiﬁcance of these issues.